(untitled) (Eurasian Journal of Ecology, 2024)
Self-purification in surface waters involves many components of the aquatic ecosystem, among which aquatic microorganisms play an important role, which perform the function of primary oxidation or reduction of pollutants entering the reservoir. However, a number of chemicals that pollute lakes and rivers inhibit the activity of bacterioplankton. This leads to the fact that the ability of the reservoir to self-cleaning is sharply violated and its degradation occurs. The activity of the process of destruction of organic substances can be judged by the oxygen parameters in the water of rivers and lakes. The purpose of this work was to study the effect of general chemical pollution of substances in natural water bodies on the ability of self-purification due to microorganisms. To assess the ability of water bodies to self-purify, the R/BOD ratio was used. The functional activity of microorganisms in the samples was assessed by their ability to reduce the ratio of dissolved oxygen on the first day R1/BOD1 and on the fifth day R5/BOD5 in the presence of test pollutants: gasoline, surfactant and antibiotic. It was shown that the decrease in the self-cleaning ability of natural waters under the influence of various pollutants from bioorganic pollution both in the river and in the lake is of a general nature. In a comparative study of the degree of suppression of heterotrophic destruction in lake and river water for gasoline, Fairy detergent and antibiotic Ospamox 250 mg, the latter most sharply reduces the ability of water bodies to bioorganic destruction at a dilution of 1:999, and at a dilution of 1:99 completely destroys it. The second most inhibiting natural water self-purification agent is Fairy detergent. When diluted 1:9 and 1:99 Fairy reduces self-cleaning ability to zero on the fifth day. Gasoline is capable of suppressing self-purification only in relatively large quantities: 1:9 in relation to water. Key words: self-purification, bacterioplankton, dissolved oxygen, BOD, surfactant.